Isolation, Characterisation And Therapeutic Efficacy of Bacteriophage Isolates Used Against Avian Pathogenic Escherichia coli in Broiler Chickens - Lau, Gee Leng (2010)
Colibacillosis is one of the main causes of economic losses in the poultry industry worldwide. Although antibiotics have been used to control this infection, the emergence of antibiotic resistant bacteria poses a threat to animal and human health. Therefore, an alternative to antibiotics is urgently required. In the present study, two bacteriophages, namely ØEC1 and ØEC2, which were lytic against avian pathogenic Escherichia coli (APEC) O78:K80 and O1:K1 (causative agent of colibacillosis), respectively, were isolated from chickens’ fecal samples. These two phages are specific to their target host bacteria and do not lyse other tested bacteria such as Escherichia coli, Salmonella, Campylobacter, Lactobacillus and several gastrointestinal microflora. Examination by transmission electron microscope revealed that ØEC1 and ØEC2 belong to Podoviridae and Tectiviriae family, respectively. Both phages demonstrated an optimum multiplicity of infection (MOI) of 0.1 to 1. Based on the results of single-step growth, the latent period of ØEC1 was 25 min with a burst size of 200 particles per infected cell. ØEC2 showed a shorter latent period of 7 min and a burst size of 2-3 particles per infected cell. Under the experimental condition, the highest adsorption rate for ØEC1 was 99.9% and ØEC2 was 82.2%. Both phages demonstrated similar optimum pH (pH 6.0 - pH 9.0) for effective phage lytic activity. The optimum temperature for ØEC1 lytic activity was found to be in the range of 25°C to 41°C while ØEC2 demonstrated the highest lytic activity at 37°C. These results indicated that ØEC1 could be a more virulent phage in comparison to ØEC2. Thus, the efficacy of ØEC1 as therapeutic agent against APEC O78:K80 was evaluated in vivo in chickens. Results from the in vivo study showed that treatment with ØEC1 could reduce the mortality rate of E. coli challenged birds by 70% during the 3 week experimental period. The body weight of birds from the E. coli challenged group treated with ØEC1 was not significantly different from those of negative control groups on day 14 post-infection and was 15.4% higher than that of untreated E. coli challenged group on day 21 post-infection. Based on the gross lesion observations for airsacculitis, pericarditis and perihepatitis, the infections were found to be less severe in the treated E. coli challenged group. The total viable cell counts of E. coli in the lungs of treated E. coli challenged birds was approximately 22-fold lower than that of untreated challenged birds at day 1 post-infection. E. coli isolation frequency from blood and organs was also found to be lower in treated birds. These results suggested that ØEC1 is effective in vivo and could be an alternative to antibiotic to treat colibacillosis in chickens.